Myopic loss aversion, disappointment aversion, and the equity premium puzzle - David Fielding; Livio Stracca (European Central Bank (ECB), 2003)
This paper takes a close look at the 'behavioural finance' explanations of the equity premium puzzle, namely myopic loss aversion (Benartzi and Thaler, 1995) and disappointment aversion (Ang, Bekaert and Liu, 2000). The paper proposes a simple specification of loss and disappointment aversion and brings these theories to the data. The main conclusion of the paper is that a highly short-sighted investment horizon is required for the historical equity premium to be explained by loss aversion, while reasonable values for disappointment aversion are found also for long investment horizons. So, stocks may lose only in the short term, but may disappoint also in the long term.
Keywords: G11; G12; 330; disappointment aversion; equity premium puzzle; investment horizon; Myopic loss aversion; reference dependence